Les locutions adverbiales figées: étude des fonctions primaires - Oueslati, Lassâad (Neophilologica, 2011)
The theory of object classes holds that every elementary sentence is inevitably constituted by elements which make this sentence acceptable. Each element has a function called a primary function. There are three such functions: predicate, argument and actualizer. These three functions can be realized by all the simple and compound, free and fixed syntactical categories. In this article we will show that the fixed adverbial sequences much as other syntactic categories can have primary functions.